Lymph node ratio as a prognostic factor for survival in patients with head and neck squamous cell carcinoma. Issue 4 (August 2018) - Sano, Daisuke; Yabuki, Kenichiro; Takahashi, Hideaki; Arai, Yasuhiro; Chiba, Yoshihiro; Tanabe, Teruhiko; Nishimura, Goshi; Oridate, Nobuhiko
Abstract: Objective: The purpose of this study is to validate the concept of lymph node ratio (LNR) in head and neck squamous cell carcinoma (HNSCC). Methods: A total of 63 patients with HNSCC who underwent resection of the primary tumor combined with neck dissection in our institution were analyzed in this study. LNR was defined as the number of positive lymph nodes divided by the total number of lymph nodes excised. LNR was categorized into two groups (<0.068 and ≥0.068) according to the results of receiver-operating characteristic plots for determination of the cut-off value. Results: LNR ≥ 0.068 was associated with poor overall survival (OS), progression-free survival (PFS) and locoregional recurrence-free survival (LRFS) after resection of the primary tumor combined with neck dissection in patients with HNSCC. Univariate and multivariate data analysis showed that LNR ≥ 0.068 was an independent prognostic factor for OS, PFS and LRFS. Both pathological T stage status (pT3 or 4) and ≥3 positive LNs were also an independent prognostic factors for PFS in patients with HNSCC in our univariate and multivariate analysis. Conclusion: These results suggested that LNR could be useful tools in identifying HNSCC patients with poor outcomes.